Neutrophil Extracellular Traps and Liver Disease - Hilscher, Moira B.; Shah, Vijay H. (Seminars in Liver Disease, 2020)
Neutrophil extracellular traps, or NETs, are heterogenous, filamentous structures which consist of extracellular DNA, granular proteins, and histones. NETs are extruded by a neutrophil in response to various stimuli. Although NETs were initially implicated in immune defense, subsequent studies have implicated NETs in a spectrum of disease processes, including autoimmune disease, thrombosis, and cancer. NETs also contribute to the pathogenesis of several common liver diseases, including alcohol-associated liver disease and portal hypertension. Although there is much interest in the therapeutic potential of NET inhibition, future clinical applications must be balanced against potential increased risk of infection.
Keywords: portal hypertension; cirrhosis; neutrophil